Multiphase force stimulation response luminescent material and preparation and application thereof
By preparing multiphase force stimulation-responsive luminescent materials, the problems of high response threshold and low contrast of existing materials are solved, and the fluorescence response with low response threshold and high contrast and multi-order response are achieved, which significantly improves the differentiated response effect of different force stimuli.
Patent Information
- Application Number
- CN202311287853.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-07
AI Technical Summary
When existing force-stimulating organic luminescent materials are used for real-time monitoring of part deformation and stress conditions, the response threshold is high and the contrast is low, so it is impossible to achieve distinctive response and multi-order response to different forces.
A multiphase force stimulation-responsive luminescent material is developed, and a luminescent material with fluorescence luminescent and fluorescence color conversion characteristics are formed by preparing compounds of formula I, and through acylation nucleophilic substitution, reduction and diazotization, Sonogashira cross-coupling and other steps.
A low response threshold and high contrast fluorescence response are achieved, which can achieve fluorescence brightness and color conversion under pressure and frictional stimulation, and achieve distinctive response and multi-order response to different forces.
Smart Images

Figure CN119775165A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of stimulus-responsive luminescent materials, and in particular relates to the preparation and application of a multi-phase force-stimulated organic luminescent material. Background Art
[0002] In the process of conducting strength tests on aircraft engine parts, it is necessary to capture the stress and strain of different parts of the parts in a timely manner in order to monitor the deformation and stress conditions of the parts in real time. At the same time, when conducting material-level or component-level mechanical tests, it is also necessary to provide real-time feedback on the stress and strain conditions of each part of the test piece in order to obtain the stress changes of the test piece during the loading and unloading process.
[0003] Stimulus-responsive luminescent materials refer to materials whose luminescent color or intensity changes significantly under the stimulation of mechanical force, temperature, pH value, water vapor, etc. When used in non-destructive pressure sensors, force-responsive luminescent materials can produce changes in luminescent wavelength or intensity according to the magnitude of the force stimulus, which enables non-destructive pressure sensors to instantly and sensitively detect the extrusion of the carrier surface.
[0004] Multiphase force-stimulated organic luminescent materials can be applied to the surface of the part or test piece to be tested. During the test, the material will emit different luminescent colors due to different forces on different parts of the part or test piece. Through high-speed photography or other recording methods, the stress distribution cloud map of the part at different test stages can be obtained. Through the stress distribution cloud map, the strength test model of the part or test piece can be calibrated, and after iteration, more accurate strength calculation results can be obtained.
[0005] After the test, the most demanding parts of the parts or test pieces will have obvious color differences from other parts, and these parts are also the most dangerous parts that cause part failure. By calibrating the key parts, the strength calculation model can be verified and the failure probability of the parts or test pieces can be evaluated.
[0006] Existing force-stimulated organic light-emitting materials have problems of high response threshold and low contrast when used for real-time monitoring of deformation and force conditions of parts. Moreover, they only monitor through fluorescence onset or fluorescence color change, and cannot achieve differentiated responses to different forces or multi-order responses. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a multi-phase force stimulation responsive luminescent material, which can achieve a low response threshold and high contrast fluorescence response when used for real-time monitoring of the deformation and force conditions of parts. The luminescent material of the present invention can achieve fluorescence light-up under pressure stimulation, and further can achieve fluorescence color change under friction stimulation, achieve differentiated response to different forces, and achieve multi-order response.
[0008] Specifically, the present invention provides a compound of formula I which can be used as a multi-phase force stimulus responsive luminescent material:
[0009]
[0010] The present invention also provides a method for preparing the compound of formula I, the method comprising the following steps:
[0011] (1) allowing 4-bromo-2-nitrophenol to undergo an acylation nucleophilic substitution reaction with 4-methoxybutyryl chloride to produce a compound of formula II;
[0012]
[0013] (2) subjecting the compound of formula II to reduction and diazotization to obtain the compound of formula III;
[0014]
[0015] (3) subjecting the compound of formula III to a Sonogashira cross-coupling reaction with trimethylsilyl acetylene to obtain a compound of formula IV;
[0016]
[0017] (4) subjecting the compound of formula IV to trimethylsilyl deprotection reaction to obtain a compound of formula V;
[0018]
[0019] (5) subjecting the compound of formula V to a Sonogashira cross-coupling reaction with 9,10-dibromoanthracene to obtain a compound of formula I.
[0020] In one or more embodiments, in step (1), the reaction solvent is dichloromethane, and the reaction is carried out in the presence of sodium hydride.
[0021] In one or more embodiments, step (2) is divided into two steps, wherein the first step is firstly carried out with ethanol as the reaction solvent in the presence of stannous chloride, and then with water as the reaction solvent in the presence of sodium hydroxide; the reaction solvent for the second step is acetonitrile and hydrochloric acid, and the second step is carried out in the presence of sodium nitrite and p-toluenesulfonyl nitrile.
[0022] In one or more embodiments, in step (3), the reaction solvent is triethylamine, and the reaction is carried out in the presence of triphenylphosphine, tetrakis(triphenylphosphine)palladium and cuprous iodide.
[0023] In one or more embodiments, in step (4), the reaction solvent is tetrahydrofuran, and the reaction is carried out in the presence of tetrabutylammonium fluoride.
[0024] In one or more embodiments, in step (5), the reaction solvent is a mixture of toluene and triethylamine, and the reaction is carried out in the presence of triphenylphosphine, tetrakis(triphenylphosphine)palladium and cuprous iodide.
[0025] The present invention also provides a luminescent material, which is a crystalline material obtained by dissolving the compound of formula I in a mixed solvent of dichloromethane and ethyl acetate and then recrystallizing.
[0026] The present invention also provides a mechanical force sensor device, comprising a test sample and a mechanoluminescent coating disposed on the surface of the test sample, wherein the mechanoluminescent coating comprises a compound of formula I or a luminescent material described in any embodiment of the present invention.
[0027] The present invention also provides use of the compound of formula I or the luminescent material described in any embodiment herein in a mechanical force sensor device.
[0028] The present invention also provides the use of the compound of formula I or the luminescent material described in any embodiment of the present invention in detecting deformation or stress conditions of parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are the photoluminescence spectra of the original sample, the slightly crushed sample, and the completely ground sample of the D1 crystal of the present invention.
[0030] Figure 2 These are photos of the original sample, slightly crushed sample and completely ground sample of the D1 crystal of the present invention under a 365 nm ultraviolet lamp.
[0031] Figure 3 It is a scatter diagram of the crushing pressure of the D1 crystal of the present invention.
[0032] Figure 4 These are the X-ray diffraction spectra of the original sample, the slightly crushed sample and the completely ground sample of the D1 crystal of the present invention.
[0033] Figure 5 The differential scanning calorimeter curves of the original sample, the slightly crushed sample and the completely ground sample of the D1 crystal of the present invention are shown in FIG.
[0034] Figure 6is a schematic diagram of a pressure sensing device in some embodiments of the present invention. Figure 5 In the figure, 1 is the D1 coating pressure sensor, 2 is the force to be measured, 3 is the sensing part of the sensor, 4 is the ultraviolet lamp, 5 is the sensor output signal, 6 is the integrated signal amplifier, 7 is the spectrometer, and 8 is the signal processing part. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0036] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0037] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0038] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0039] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0040] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0041] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0042] The molecular structure of the multiphase force stimulus responsive luminescent material (hereinafter referred to as luminescent material) provided by the present invention is based on a phenyl-ethynyl-anthracene planar conjugated molecule as a skeleton. The chemical structural formula of the luminescent material of the present invention is shown in Formula I:
[0043]
[0044] The chemical name of the compound of formula I is anthracene-9,10-diylbis(ethynyl-2,1-diyl)bis(2-cyano-4,1-phenylene)bis(4-methoxybutyrate), also known as compound DCPM.
[0045] The compound of formula I can be prepared by a method comprising the following steps:
[0046] (1) allowing 4-bromo-2-nitrophenol to undergo an acylation nucleophilic substitution reaction with 4-methoxybutyryl chloride to produce a compound of formula II;
[0047]
[0048] (2) subjecting the compound of formula II to reduction and diazotization to obtain the compound of formula III;
[0049]
[0050] (3) subjecting the compound of formula III to a Sonogashira cross-coupling reaction with trimethylsilyl acetylene to obtain a compound of formula IV;
[0051]
[0052] (4) subjecting the compound of formula IV to trimethylsilyl deprotection reaction to obtain a compound of formula V;
[0053]
[0054] (5) subjecting the compound of formula V to a Sonogashira cross-coupling reaction with 9,10-dibromoanthracene to obtain a compound of formula I.
[0055] In step (1), 4-bromo-2-nitrophenol and 4-methoxybutyryl chloride undergo acylation nucleophilic substitution reaction in dichloromethane (DCM) under the action of sodium hydride to generate an intermediate product 4-bromo-2-nitrophenyl-4-methoxybutyrate (compound of formula II).
[0056] Preferably, in step (1), the acylation nucleophilic substitution reaction is as follows: 4-bromo-2-nitrophenol and 4-methoxybutyryl chloride are dissolved in dichloromethane, and after nitrogen replacement, sodium hydride is slowly added in an ice-water bath, and stirred at room temperature for 12±2 hours, and the reaction is monitored by thin layer chromatography until the raw material point disappears; water is added to quench the reaction, and the organic phase is extracted with dichloromethane, dried over anhydrous magnesium sulfate, and filtered; after evaporating the solvent under reduced pressure, the crude product is purified by a chromatography column using petroleum ether:ethyl acetate as an eluent to obtain a white solid.
[0057] In step (2), the reaction is carried out in two steps: the first step is a reduction reaction, and the second step is a diazotization reaction. In the reduction reaction, ethanol is first used as a reaction solvent to react the compound of formula II with stannous chloride, and then the solvent ethanol is evaporated, and the reaction product is reacted with sodium hydroxide in water to cause the compound of formula II to undergo a reduction reaction first. In the diazotization reaction, the reduction reaction product is subjected to a diazotization reaction under low temperature conditions with acetonitrile and hydrochloric acid as reaction solvents, sodium nitrite and tosyl nitrile as reaction reagents to obtain a compound of formula III.
[0058] Preferably, in step (2), the reduction reaction is as follows: under nitrogen protection, the compound of formula II and stannous chloride are dissolved in ethanol, reacted at 80±5°C for 2±1 hours, and after the solvent ethanol is evaporated, a 20±5wt% NaOH aqueous solution is added and reacted at room temperature for 2±1 hours. After the reaction is completed, the organic phase is extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and evaporated to dryness under reduced pressure. The diazotization reaction is as follows: the product obtained in the previous step is dissolved in acetonitrile, hydrochloric acid is added thereto, cooled to -10±1°C, sodium nitrite is added to react for 3±1 hours, and then p-toluenesulfonyl nitrile is added to react at room temperature for 2±1 hours. After the reaction is completed, the organic phase is extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and purified by column chromatography (petroleum ether: ethyl acetate) to obtain a white solid.
[0059] In step (3), triethylamine is used as a reaction solvent, triphenylphosphine, tetrakis(triphenylphosphine)palladium, and cuprous iodide are used as catalysts, and the compound of formula III is subjected to a Sonogashira cross-coupling reaction with trimethylsilyl acetylene under anhydrous and oxygen-free conditions to obtain a compound of formula IV. In the present invention, the Sonogashira cross-coupling reaction is known, also known as the Sonogashira coupling reaction, the Sonogashira-Hagihara coupling reaction, and is a cross-coupling reaction of an organic halide and a terminal alkyne catalyzed by Pd / Cu.
[0060] Preferably, in step (3), the Sonogashira cross-coupling reaction is as follows: take dried and redistilled triethylamine, deoxygenate by bubbling nitrogen below the liquid surface, then sequentially add the compound of formula III, catalyst triphenylphosphine, cuprous iodide, and tetrakis(triphenylphosphine)palladium to the system under bubbling conditions, replace with nitrogen, and finally add trimethylsilyl acetylene, raise the temperature to 65-70°C in anhydrous and oxygen-free conditions under nitrogen protection, and stir to react for 12±2 hours; after cooling the reaction system to room temperature, concentrate the resulting reaction mixture using a rotary evaporator to remove the solvent, dissolve the residue with ethyl acetate, wash the organic layer with dilute hydrochloric acid, saturated sodium bicarbonate solution and saturated sodium chloride solution in sequence, dry with anhydrous magnesium sulfate, and filter; after evaporating the solvent under reduced pressure, purify the crude product with a chromatography column using petroleum ether:ethyl acetate as an eluent to obtain a light yellow solid.
[0061] In step (4), tetrahydrofuran (THF) is used as the reaction solvent, tetrabutylammonium fluoride is added to the reaction system, and trimethylsilyl deprotection reaction is performed on the compound of formula IV to generate the compound of formula V.
[0062] Preferably, in step (4), the trimethylsilyl deprotection reaction is as follows: adding the compound of formula IV to dry redistilled tetrahydrofuran, after nitrogen replacement, adding a tetrahydrofuran solution of tetrabutylammonium fluoride into the reaction bottle by syringe, sealing the system with nitrogen and protecting it from light, and stirring the reaction at room temperature; after the reaction is completed as monitored by thin layer chromatography, water is added to quench the reaction, the solution is washed with a saturated sodium chloride solution, dried over anhydrous magnesium sulfate, filtered, and the solvent is evaporated under reduced pressure. After that, the crude product is purified by a chromatographic column using petroleum ether:ethyl acetate as an eluent to obtain a light yellow solid.
[0063] In step (5), the compound of formula V is used as a raw material, toluene and triethylamine are used as a mixed reaction solvent, triphenylphosphine, tetrakis(triphenylphosphine)palladium, and cuprous iodide are used as catalysts, and a Sonogashira cross-coupling reaction is carried out with 9,10-dibromoanthracene under anhydrous and oxygen-free conditions to obtain a compound of formula I.
[0064] Preferably, in step (5), the Sonogashira cross-coupling reaction is as follows: take dried and redistilled triethylamine and toluene, bubble nitrogen below the liquid surface of the mixed solution to deoxygenate, then sequentially add 9,10-dibromoanthracene, compound of formula V, triphenylphosphine, cuprous iodide, and tetrakis(triphenylphosphine)palladium to the system under bubbling conditions, evacuate the system and pass nitrogen three times, raise the temperature to 65-70°C under nitrogen protection, and stir to react for 12±2 hours; monitor the reaction by thin layer chromatography, and after the reaction is completed, cool the reaction system to room temperature; evaporate the solvent under reduced pressure, dissolve the residue with ethyl acetate, wash the organic layer with dilute hydrochloric acid, saturated sodium bicarbonate solution, and saturated sodium chloride solution in turn, dry with anhydrous magnesium sulfate, and filter; evaporate the solvent under reduced pressure, purify the crude product with a chromatography column, and use petroleum ether:ethyl acetate as an eluent to obtain a bright yellow solid.
[0065] The compound of formula I of the present invention is dissolved in a mixed solvent of dichloromethane and ethyl acetate and recrystallized to obtain a crystalline material (also referred to as D1 crystal herein). The material can achieve a fluorescence light-on response to pressure, and further can achieve a fluorescence color change response when a friction force is applied, and can be used as a multi-phase force stimulation response luminescent material. Preferably, the recrystallization is carried out in a mixed solvent of dichloromethane and ethyl acetate with a volume ratio of 1:7-1:9, for example, 1:8. In some preferred embodiments, the recrystallization comprises: adding the compound of formula I to a mixed solvent of dichloromethane and ethyl acetate in batches at 40±5°C to prepare a saturated solution; slowly cooling the solution to room temperature, and after standing for 3±1 days, obtaining D1 crystals.
[0066] The present invention also provides the use of the luminescent material of the present invention in preparing a mechanical force sensor device, such as a pressure sensor. The pressure sensor may include a pressure sensing element and a luminescent signal processing element.
[0067] The method for pressure detection using a pressure sensor comprising the luminescent material of the present invention may include the following steps:
[0068] (1) dissolving the compound of formula I of the present invention in a mixed solution of dichloromethane and ethyl acetate to obtain a crystalline material by recrystallization, or providing the crystalline material of the present invention;
[0069] (2) Using different mechanical forces to stimulate the crystal material, the quantitative relationship between the intensity of mechanoluminescence and the magnitude of the applied stress is fitted as the basic parameter of the luminescence signal processing element;
[0070] (3) Sensor input and output:
[0071] The luminescent material of the present invention is arranged on a carrier plate to form a coating to form a force-induced luminescent material layer. Under the irradiation of ultraviolet light, the original luminescent wavelength of the force-induced luminescent material layer is λ=560nm, and the light signal is received by a designated signal acquisition device to display state S0; when the sample is stimulated by force, the luminescent emission peak changes instantaneously, and at this time the signal is received by the designated signal acquisition device to display state S1; only one of the above display states is a valid signal output at the same time.
[0072] In a preferred embodiment, the display state S0 is only an integrated display of a light signal with a light emission wavelength of 560 nm.
[0073] In a preferred embodiment, the display state S1 is simply an integrated display of the optical signal that determines the emission peak.
[0074] In a preferred embodiment, the ultraviolet lamp emits light at a wavelength of 358 nm.
[0075] The multi-phase force stimulus responsive luminescent material provided by the present invention has the property of homogeneous polycrystal, and recrystallization in different solvents can form multiple initial states with different crystal phase structures. Among them, after the D1 crystal is subjected to force stimulation, a light-on signal change from a dark state to a bright state is realized, and multiple reversible conversions from orange to green can be realized through mechanical grinding and solvent fumigation. During the action of force stimuli of different intensities, the luminescent material of the present invention can undergo multiple changes in fluorescence intensity or color, and the fluorescence intensity and color contrast are obvious. Different from the general excitation-responsive organic luminescent material that only undergoes a single wavelength change process, the luminescent material of the present invention has three states with very different luminescent properties, and can realize reversible luminescence conversion through means such as solvent fumigation. This characteristic is very suitable for lossless pressure sensor devices, and has important application prospects in the field of sensing with high sensitivity requirements and timely information transmission requirements.
[0076] The luminescent material of the present invention can be applied to the surface of the part or test piece to be tested. During the test, since different parts of the part or test piece are subjected to different forces, the material will present different luminescent colors. By high-speed photography or other recording means, the stress distribution cloud map of the part at different test stages can be obtained. Through the stress distribution cloud map, the strength test model of the part or test piece can be calibrated, and after iteration, a more accurate strength calculation result can be obtained. After the test, the most demanding parts of the part or test piece will have obvious color differences from other parts, and these parts are also the most dangerous parts that cause part failure. By calibrating the key parts, the strength calculation model can be verified and the failure probability of the part or test piece can be evaluated.
[0077] The luminescent material of the present invention can achieve a fluorescence on-off response to pressure, with a response threshold lower than 1MPa; further, when a friction force is applied, a fluorescence color change response can be achieved. Therefore, the luminescent material of the present invention can achieve a three-order fluorescence force stimulation response of on-off-color change.
[0078] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0079] Example 1
[0080] This example prepares the compound of formula I by the following steps:
[0081] (1) Synthesis of compound of formula II
[0082]
[0083] 4-Bromo-2-nitrophenol (9.17mmol, 2.0g), 4-methoxybutyryl chloride (10.00mmol, 1.36g) were dissolved in dichloromethane (50mL), and after evacuating nitrogen three times, sodium hydride (13.87mmol, 0.33g) was slowly added under ice-water bath conditions. Stir for 12 hours at room temperature, and monitor the reaction until the raw material point disappears by thin layer chromatography. Water was added to quench the reaction, and the organic phase was extracted with dichloromethane, dried over anhydrous magnesium sulfate, and filtered. After the solvent was evaporated under reduced pressure, the crude product was purified by chromatography column, and petroleum ether: ethyl acetate (20:1, v:v) was used as eluent to obtain 2.71g of white solid, with a yield of 93%. 1 H NMR (600 MHz, CDCl 3 )δ8.45(d,J=1.8Hz,1H),7.97(dd,J=7.8,1.8Hz,1H),7.30(d,J=7.8Hz,1H),3.35(t,J=4.5Hz,2H),3.23(s,3H),2.52(t,J=4.5Hz,2H),1.95(m,2H). 13 C NMR (125 MHz, CDCl 3 )δ172.31,144.92,144.30,138.11,127.25,124.77,119.40,71.70,59.33,29.89,24.42.
[0084] (2) Synthesis of the compound of formula III (4-bromo-2-cyanophenyl-4-methoxybutyrate)
[0085]
[0086] Under nitrogen protection, the compound of formula II (1.60 g, 5 mmol) was reacted with SnCl 2 ·2H 2 O (5.64 g, 25 mmol) was dissolved in ethanol (25 mL), reacted at 80 ° C for 2.5 hours, and the solvent was evaporated under reduced pressure. An excess of 20 wt% NaOH aqueous solution was added to the residue under ice bath and stirred at room temperature for 2 hours. The organic phase was extracted with ethyl acetate and dried over anhydrous magnesium sulfate. The solvent was evaporated under reduced pressure, and the obtained solid product was directly used for the next reaction.
[0087] The solid product obtained in the previous step was dissolved in acetonitrile (6 mL), and hydrochloric acid (6 mol / L, 5 mL) and NaNO were added at -10 °C. 2 (0.42g, 6mmol), react for 2 hours. The mixture was added in batches to an acetonitrile solution of p-toluenesulfonyl nitrile (1.81g, 10mmol), and reacted at room temperature for 2 hours. After the reaction was completed, the reaction was quenched with water, and the organic phase was extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and purified by column chromatography (petroleum ether: ethyl acetate). 1.02g of white solid was obtained with a yield of 69%. 1 H NMR (600 MHz, CDCl 3 )δ7.86(dd,J=7.8,1.8Hz,1H),7.76(d,J=1.8Hz,1H),7.22(d,J=7.8Hz,1H),3.35(t,J=4.5Hz,2H),3.23(s,3H),2.52(t,J=4.5Hz,2H),1.95(m,2H). 13 C NMR (125 Hz, CDCl 3 )δ172.31,151.26,136.39,133.72,124.58,120.62,115.82,110.71,71.7,59.3,29.8,24.4.
[0088] (3) Synthesis of the compound of formula IV (2-cyano-4-(trimethylsilyl)ethynylphenyl-4-methoxybutyrate)
[0089]
[0090] Take dried and redistilled triethylamine (38 mL), bubble nitrogen below the liquid surface (about 1-2 / sec) for 0.5 h, then add compound III (6.76 mmol, 2.02 g), triphenylphosphine (0.99 mmol, 0.24 g), cuprous iodide (0.59 mmol, 0.1 g) and tetrakis(triphenylphosphine)palladium (0.46 mmol, 0.54 g) into the system in sequence under bubbling conditions, evacuate and pass nitrogen three times, finally add trimethylsilyl acetylene (15.38 mmol, 1.5 g), heat to 70° C. under nitrogen protection, stir and react for 12 hours. After the reaction system is cooled to room temperature, the resulting reaction mixture is concentrated to remove the solvent using a rotary evaporator, the residue is dissolved with ethyl acetate, the organic layer is washed with 5 wt% hydrochloric acid, saturated sodium bicarbonate solution and saturated sodium chloride solution in sequence, dried over anhydrous magnesium sulfate, and filtered. The solvent was evaporated under reduced pressure and the crude product was purified by chromatography using petroleum ether:ethyl acetate (20:1, v:v) as eluent to obtain 0.89 g of a light yellow solid with a yield of 41%. 1 H NMR (600 MHz, CDCl 3 )δ7.72(dd,J=7.8,1.8Hz,1H),7.42(d,J=1.8Hz,1H),7.30(d,J=7.8Hz,1H),3.35(t ,J=4.5Hz,2H),3.23(s,3H),2.52(t,J=4.5Hz,2H),1.97-1.93(m,2H),0.08(s,9H). 13 C NMR (125 MHz, CDCl 3 )δ172.33,152.02,137.11,136.46,121.91,120.22,115.81,108.11,98.94,71.77,59.32,53.53,29.80,24.41,3.40.
[0091] (4) Synthesis of Compound V
[0092]
[0093] The compound of formula IV (4.87mmol, 1.54g) was added to dry redistilled tetrahydrofuran (20mL), and after evacuating the mixture and passing nitrogen three times, a tetrahydrofuran solution of tetrabutylammonium fluoride (1mol / L, 10mL) was added to the reaction bottle by syringe, the system was sealed with nitrogen and protected from light, and the reaction was stirred at room temperature. After the reaction was complete by thin layer chromatography, water was added to quench the reaction, the solution was washed with saturated sodium chloride solution, dried over anhydrous magnesium sulfate, filtered, and the solvent was evaporated under reduced pressure. The crude product was purified by chromatographic column, and petroleum ether: ethyl acetate (20:1, v:v) was used as the eluent to obtain 1.14g of a light yellow solid with a yield of 96%. 1 H NMR (600 MHz, CDCl 3 )δ7.74(dd,J=7.8,1.8Hz,1H),7.44(d,J=1.8Hz,1H),7.31(d,J=7.8Hz,1H),4.08(s ,1H),3.35(t,J=4.5Hz,2H),3.23(s,3H),2.52(t,J=4.5Hz,2H),1.96-1.93(m,2H). 13 C NMR (125 MHz, CDCl 3 )δ172.34,152.04,137.03,136.51,121.91,120.32,115.81,108.11,82.33,81.49,71.76,59.32,29.80,24.41.
[0094] (5) Synthesis of compound DCPM (compound of formula I)
[0095]
[0096] Take dried and redistilled triethylamine (20mL) and toluene (40mL), and bubble nitrogen (about 1-2 / second) under the surface of the mixed solution for 0.5h, then add 9,10-dibromoanthracene (1.49mmol, 0.5g), compound of formula V (3.73mmol, 0.92g), triphenylphosphine (0.36mmol, 0.09g), cuprous iodide (0.18mmol, 0.03g), tetrakis(triphenylphosphine)palladium (0.09mmol, 0.10g) to the system in sequence under bubbling conditions, evacuate and pass nitrogen three times, and heat to 65-70℃ under nitrogen protection and stir to react for 12 hours. Monitor the reaction by thin layer chromatography, and after the reaction is completed, cool the reaction system to room temperature. Evaporate the solvent under reduced pressure, dissolve the residue with ethyl acetate, wash the organic layer with 5wt% hydrochloric acid, saturated sodium bicarbonate solution and saturated sodium chloride solution in sequence, dry with anhydrous magnesium sulfate, and filter. The solvent was evaporated under reduced pressure and the crude product was purified by chromatography using petroleum ether:ethyl acetate (8:1, v:v) as eluent to obtain 0.69 g of a bright yellow solid with a yield of 80%. 1 H NMR (600 MHz, CDCl 3 )δ8.47(dd,J=7.8,1.7Hz,4H),7.77(dd,J=8.0,1.8Hz,2H),7.63–7.59(m,4H),7.46(d,J=1.7Hz,2 H),7.29(d,J=8.0Hz,2H),3.35(t,J=4.5Hz,4H),3.23(s,6H),2.52(t,J=4.6Hz,4H),1.95(m,4H). 13 C NMR (101 MHz, CDCl 3 )δ172.33,152.09,139.33,137.01,136.44,135.33,135.14,128.89,128. 13,121.91,120.20,119.71,115.84,108.11,71.74,59.35,29.84,24.41.
[0097] Example 2
[0098] The compound DCPM was recrystallized from a mixed solvent of dichloromethane and ethyl acetate to obtain a D1 crystal sample. The specific operation was as follows: at 40°C, DCPM was added in batches to a mixed solvent of dichloromethane and ethyl acetate (ratio 1:8, v:v) to prepare a saturated solution. The solution was slowly cooled to room temperature and allowed to stand for about 3 days to obtain D1 crystals.
[0099] The compound DCPM of the present invention has a homogeneous polymorphic property. D1 is selected as a sample to test its color change under force stimulation.
[0100] Test Example 1
[0101] The D1 sample was crushed and ground, and the photoluminescence (PL) spectra of the original sample, the slightly crushed sample, and the completely ground sample were tested. The results are as follows: Figure 1 shown.
[0102] The testing method of PL spectrum is: the excitation wavelength is selected as 358nm, the fluorescence spectrum wavelength range is selected as 400-700nm, the appropriate light path slit and scanning speed are selected according to the instrument signal, and the photoluminescence spectrum of the sample is tested.
[0103] In this article, slight crushing refers to applying positive pressure to the crystals to crush them into small grains of irregular shape and size, with a particle size of about 1-3 mm. Complete grinding refers to applying grinding force to the crushed grains to further grind the small grains into powder.
[0104] Depend on Figure 1 It can be seen that D1 exhibits a multi-phase reversible transition in mechanical stimulation response luminescence process: the maximum emission wavelength of the original crystal sample is 560nm, and the fluorescence emission intensity is extremely low; after slight crushing, its maximum emission wavelength blue-shifts to 539nm, and the fluorescence emission intensity also increases significantly; after complete grinding, the maximum emission wavelength red-shifts to 578nm, and the fluorescence emission intensity remains basically unchanged.
[0105] The photos of the original sample, slightly crushed sample and completely ground sample under 365nm UV light are shown in the figure below. Figure 2 As shown, it can be seen that from the original state to slightly crushed and then to completely ground, the fluorescence color changes from dark yellow to bright green and then to orange. After the completely ground sample is fumigated with dichloromethane solvent, the color changes from orange to green. The solvent fumigation operation is: the dichloromethane solvent is placed on a 35°C heating table, the ground sample is placed above the solvent, and the sample is fumigated by the solvent volatilization.
[0106] Test Example 2
[0107] Test the positive pressure required for crystal crushing. The test results are as follows: Figure 3 As shown, it can be seen that the force required for the D1 sample to start luminescence is in the kilopascal range, which is less than 1 MPa.
[0108] The test method for the crystal crushing positive pressure is: use a weight to apply a quantifiable pressure under a microscope to cause the crystal to slightly break, and repeat 8 times to obtain a crushing pressure scatter plot.
[0109] Depend on Figure 3It can be seen that in this paper, a weight (20±10g) was used to apply pressure under a microscope, and it was found that the crystal (1.5±0.5*1.5±0.5mm) was slightly broken, and it was clearly observed under the microscope that the new surface of the crystal after the crystal was broken emitted yellow-green light. It was calculated that the pressure required for the D1 sample to light up was in the range of 250-500KPa, which was less than 1MPa.
[0110] Test Example 3
[0111] The D1 sample was crushed and ground, and the X-ray diffraction spectra of the original sample, the slightly crushed sample, and the completely ground sample were tested. The results are as follows: Figure 4 shown.
[0112] The test method of the X-ray diffraction spectrum is: the scanning range is set to 5-40°, the scanning mode is continuous scanning, the scanning speed is 2.0000deg / min, the sample tilt angle is 0.0500deg, and the adjustment time is 1.50sec to test the X-ray diffraction spectrum of the sample.
[0113] Depend on Figure 4 It can be seen that the changes in the X-ray diffraction spectrum of D1 under mechanical crushing and grinding stimulation correspond to the changes in the fluorescence emission spectrum. The diffraction peak in the original state shows a fine structure with high crystallinity, and the diffraction peak is mainly located at 2θ = 12.78° 2θ=23.75° 2θ=25.83° and 2θ=26.77° This phenomenon can be verified from single crystal data and crystal photos. After the crystal is slightly broken by mechanical force, the sharp diffraction peak at the same position in the original crystal state changes in intensity, and weaker diffraction peaks appear at other angles 2θ=8.87° 2θ=12.86° 2θ=22.96° 2θ=25.88° and 2θ=29.16° This indicates that another crystalline state appeared as an intermediate state before mechanical grinding. This intermediate state breaks the interaction force of molecules in the original crystal that is not conducive to luminescence, reduces the order of molecular arrangement and stacking, and thus achieves the purpose of fluorescence. Then the broken sample is ground again, and the diffraction peak of the sample basically disappears, and the diffraction peak with the highest intensity moves to a small angle of 2θ = 24.94° The position of the D1 crystal sample is changed from highly ordered to gradually reduced in crystallinity through mechanical crushing and grinding stimulation. This change may be the main reason for the multi-phase stimulus response luminescence phenomenon.
[0114] Test Example 4
[0115] The D1 sample was crushed and ground, and the differential scanning calorimeter (DSC) curves of the original sample, the slightly crushed sample, and the completely ground sample were tested. The results are as follows: Figure 5 shown.
[0116] The testing method of DSC curve is as follows: the protective gas is nitrogen, the gas flow rate is selected to be 50 mL / min, the heating rate is set to be 10°C / min, and the DSC curve is drawn during the first cycle of heating process.
[0117] Figure 5 It was proved that in the process of slightly crushing the crystals of D1, the sample reached a transitional intermediate state, which was manifested in the DSC curve as the presence of an endothermic peak of 148.23°C (ΔH=32.89 J / g) different from the original state before melting, while the endothermic peak disappeared after melting.
[0118] Application Examples
[0119] This application example provides a pressure sensing device, the structure of which is as follows: Figure 6 As shown. The pressure sensing device includes a sensor sensing part 3, an integrated signal amplifier 6 and a signal processing part 8, wherein the sensor sensing part 3 includes a D1 coating pressure sensor 1 and an ultraviolet lamp 4, and the signal processing part 8 includes a spectrometer 7. After receiving the stimulation of the force to be measured 2, the D1 coating pressure sensor 1 generates a sensor output signal 5, and the sensor output signal 5 is transmitted to the spectrometer 7 through the integrated signal amplifier 6.
[0120] In the pressure sensing device, the characteristic of D1 luminescence conversion is used to produce a numerical relationship between the force stimulation size and the luminescence intensity. Under the irradiation of ultraviolet lamp 4, D1 acts as a sensor to receive the force 2 stimulus to be measured and converts it into light with different emission peaks. An optical signal processor is used to instantly and completely record the signal emission peak, and the size of the received force is judged based on its redshift or blueshift relative to the ground state.
[0121] In the initial state, D1 is not stimulated by force under the irradiation of the ultraviolet lamp 4, and the emission peak is 560nm. The fluorescence quantum yield in this state is extremely low, and the signal integration display state is S0. When the signal acquisition device is identified to have not collected any signal, the signal acquisition device is controlled to be turned off. When force is stimulated on D1, when D1 responds to the force stimulation, the signal acquisition device is in a working state to identify it, thereby determining the force magnitude of the D1 coating pressure sensor 1.
Claims
1. Compounds of formula I:
2. A method for preparing the compound of formula I according to claim 1, characterized in that: The method comprises the following steps: (1) allowing 4-bromo-2-nitrophenol to undergo an acylation nucleophilic substitution reaction with 4-methoxybutyryl chloride to produce a compound of formula II; (2) subjecting the compound of formula II to reduction and diazotization to obtain a compound of formula III; (3) subjecting the compound of formula III to a Sonogashira cross-coupling reaction with trimethylsilyl acetylene to obtain a compound of formula IV; (4) subjecting the compound of formula IV to trimethylsilyl deprotection reaction to obtain a compound of formula V; (5) subjecting the compound of formula V to a Sonogashira cross-coupling reaction with 9,10-dibromoanthracene to obtain a compound of formula I.
3. The method according to claim 2, characterized in that In step (1), the reaction solvent is dichloromethane, and the reaction is carried out in the presence of sodium hydride.
4. The method according to claim 2, characterized in that Step (2) comprises two steps of reaction, wherein the first step of the reaction is firstly carried out with ethanol as the reaction solvent in the presence of stannous chloride, and then carried out with water as the reaction solvent in the presence of sodium hydroxide; the reaction solvent of the second step of the reaction is acetonitrile and hydrochloric acid, and the second step of the reaction is carried out in the presence of sodium nitrite and p-toluenesulfonyl nitrile.
5. The method according to claim 2, characterized in that In step (3), the reaction solvent is triethylamine, and the reaction is carried out in the presence of triphenylphosphine, tetrakis(triphenylphosphine)palladium and cuprous iodide.
6. The method according to claim 2, characterized in that In step (4), the reaction solvent is tetrahydrofuran, and the reaction is carried out in the presence of tetrabutylammonium fluoride.
7. The method according to claim 2, characterized in that In step (5), the reaction solvent is a mixture of toluene and triethylamine, and the reaction is carried out in the presence of triphenylphosphine, tetrakis(triphenylphosphine)palladium and cuprous iodide.
8. A luminescent material, characterized in that: The luminescent material is a crystalline material obtained by dissolving the compound of formula I according to claim 1 in a mixed solvent of dichloromethane and ethyl acetate and then recrystallizing.
9. A mechanical force sensor device, characterized in that: The mechanical force sensor device comprises a test sample and a mechanoluminescent coating disposed on the surface of the test sample, wherein the mechanoluminescent coating comprises the compound of formula I according to claim 1 or the luminescent material according to claim 8.
10. Use of the compound of formula I according to claim 1 or the luminescent material according to claim 8 in a mechanical force sensor device or in detecting deformation or force conditions of parts.
Citation Information
Patent Citations
Pressure-induced discoloration fluorescent molecule and preparation method thereof
CN111499573A
Polymerizable mesogenic tolanes
US6514578B1